Easy Abacus Calculation in Early Childhood to Support Executive Function: An Educational Pilot Case Study of Comparing Brain Activity in the Prefrontal Cortex - Watanabe, Nobuki (Frontiers in Education, 2021)
The development of executive functions is remarkable in early childhood. Therefore, research on how to support the development of executive functions is actively being conducted. It has already been indicated that executive functions are related to the prefrontal cortex. Recent evidence suggests that the prefrontal cortex is involved in mental abacus (MA). Further, the study of the abacus—the base of MA—is good for not only mathematics but also nurturing the brain. However, although the abacus is easy to learn, learning opportunities have shrunk because of the widespread use of calculators. Through this educational pilot case study, I examined whether it is possible that even easy calculations during the introduction of abacus calculation in early childhood may have an effect on executive function support. I measured the activation of cerebral blood flow in the prefrontal cortex of a young child while he worked on the Wechsler Intelligence Scale for Children-IV; Working Memory Index tasks (forward digit-span task, backward digit-span task, and letter–number sequencing task); and the abacus calculation task using HOT-2000 (NeU, Japan), a two-channel wearable functional near-infrared spectroscopy device. The results revealed a significant difference between the abacus calculation task and the forward digit-span task; however, there was no significant difference between the abacus calculation task and other tasks. In other words, the brain in the prefrontal cortex was more activated in the abacus task than in the forward digit-span task. Difficulty levels were found to be in the order of the forward digit-span task, backward digit-span task, and letter–number sequencing task. Thus, there is a possibility that even simple abacus calculation has a positive effect on executive functions, especially working memory support, in early childhood. This study’s results provide a breakthrough in cognitive psychology, educational psychology, neuropsychology, and other fields related to child support, which are struggling to find valuable, practical practices for children in the field (i.e., schools and homes) beyond the laboratory.